Frequent unregulated use of antibiotics in rural Cambodian infants. (20th April 2020) - Miyazaki, Asuka; Tung, Rathavy; Taing, Bunsreng; Matsui, Mitsuaki; Iwamoto, Azusa; Cox, Sharon E
Abstract: Background: Despite a high prevalence of antibiotic resistance in Cambodia, few studies have assessed health-seeking behaviour and the use of antibiotics by caregivers of young children in Cambodia. Methods: We conducted a cross-sectional survey of infants <12 months of age and their caregivers, assessing the frequency of reported illness, common symptoms and associated health-seeking behaviour through structured questionnaires administered by trained fieldworkers at a home visit. In a subset of these participants, ages 4–8 months with no acute malnutrition, we conducted a 3-month surveillance with fortnightly home visits. Results: Of 149 infants (ages 1–11 months, 54.4% male) enrolled in the cross-sectional study, 76 (51.4%) reported symptoms of diarrhoea, fever or cough in the previous 14 d, with associated use of antibiotics reported in 22 (14.8%) infants. In 47 infants enrolled in the longitudinal surveillance, there were 141 reported episodes of illness in 44 (94%) infants with 21 infants (45%) reported to have received antibiotics in 32/141 (22.7%) episodes. Amoxicillin was the most commonly reported antibiotic in both surveys (68% [40/59 episodes reporting the use of antibiotics]). Conclusions: Antibiotic usage is high in this population and appears to be occurring largely outside of the formal healthcare system.